Analisis Tingkat Kematangan (Maturity Level) Layanan TI Menggunakan ITIL V4 pada PT Pertamina Patra Niaga Regional Sumbagsel - Mutiara Astri Pradina; Dicky Pratama (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Information technology services have an important role in supporting operational activities and digital services at PT Pertamina Patra Niaga Regional Sumbagsel through the MyPertamina application. However, several service disruptions are still encountered, such as server downtime, database errors, system bugs, login failures, and delays in transaction verification, which affect service quality and operational effectiveness. This study aims to analyze the maturity level of information technology services using the ITIL V4 framework, focusing on Incident Management and Problem Management practices. The research employed a mixed methods approach with descriptive analysis through observation, interviews, questionnaires, SWOT analysis, RACI mapping, maturity level assessment, and gap analysis. The results indicate that Incident Management obtained a maturity value of 3.09 and Problem Management obtained 2.91, both categorized at Level 3 (Defined Process). These findings show that service management processes have been implemented and documented properly, although several aspects still require improvement, particularly in monitoring, documentation, root cause analysis, and process evaluation. Therefore, the implementation of ITIL V4 practices is expected to improve the effectiveness, consistency, and quality of information technology service management within the organization.